2023
DOI: 10.3389/fimmu.2023.1111960
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for targeting ACKR1 in cancer and other diseases

Abstract: The chemokine network is comprised of a family of signal proteins that encode messages for cells displaying chemokine G-protein coupled receptors (GPCRs). The diversity of effects on cellular functions, particularly directed migration of different cell types to sites of inflammation, is enabled by different combinations of chemokines activating signal transduction cascades on cells displaying a combination of receptors. These signals can contribute to autoimmune disease or be hijacked in cancer to stimulate ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 178 publications
0
3
0
Order By: Relevance
“…25,26 By acting as scavenger receptor, ACKR1 modulates the bioavailability of cytokines and thereby affects inflammatory responses. 27,28 The identified associations were driven by rs12075, a well-characterized missense variant in ACKR1, resulting in less efficient chemokine binding to ACKR1 due to loss of a necessary amino-acid sulfation ( Figure 6a ). 29 The impaired receptor binding leads to elevated circulatory levels of chemokines and might in turn result in a compensatory increase in ACKR1 expression which could explain the positive association between genetically proxied ACKR1 and its ligands.…”
Section: Resultsmentioning
confidence: 99%
“…25,26 By acting as scavenger receptor, ACKR1 modulates the bioavailability of cytokines and thereby affects inflammatory responses. 27,28 The identified associations were driven by rs12075, a well-characterized missense variant in ACKR1, resulting in less efficient chemokine binding to ACKR1 due to loss of a necessary amino-acid sulfation ( Figure 6a ). 29 The impaired receptor binding leads to elevated circulatory levels of chemokines and might in turn result in a compensatory increase in ACKR1 expression which could explain the positive association between genetically proxied ACKR1 and its ligands.…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with previous studies, we demonstrated the accumulation of lymphocytes in the adventitia 47,48 . However, with the unbiased approach of spatial transcriptomics, we analyzed their potential interactions with adventitial endothelial cells and pericytes and found that the Major Histocompatibility Complex II, which can support the antigen- presentation and facilitate the adaptive immune response 21,49 and the expression of ACKR1, which might be involved in angiogenesis, chemotaxis, and cellular retention signals 50 were higher expressed in adventitial than in luminal endothelium. Notably, pericytes have also been demonstrated as antigen-presenting and cells for T- lymphocytes 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Considering that our data suggests ACKR1 to be mainly expressed on endothelium in the prostate and the observed increased immune cell infiltration a similar role in the prostate as in the lungs appears plausible. Interestingly, ACKR1's role in cancer has been reported as dominantly protective against tumor metastasis, increased proliferation, and is associated with positive outcomes [35]. Nevertheless, in PCa reduced ACRK1 expression on erythrocytes in men of African descent appeared not to be linked to aggressiveness [36,37] while ACKR1-deficient mice showed increased tumor growth [38].…”
Section: Chemokine Receptor Ackr1 Dominant Receptor Of Cxc-chemokines...mentioning
confidence: 99%